PERSOALAN IDENTITAS SOSIAL TOKOH LAKI-LAKI DALAM NOVEL PERSIDEN KARYA WISRAN HADI - Novelly, Yustity Ayu; Samsiarni, Samsiarni; Septia, Emil (Universitas Andalas, 2020)
This research is based on the background to find out what things that affect the social identity problems which faced by Minangkabau male personage in the novel Persiden which created by Wisran Hadi. This research focused on the issue of male social identity in the novel Persiden. The aimed of this research are, to describe the (1) misidentification; (2) social comparison, and (3) social mobility of male personage in the novel Persiden. The type of the research is qualitative research. The method which be used in this research is descriptive method. The results of this study indicated that there are 3 issues of social identity experienced by male personage in the Persiden novel. In accordance based on theories of the social identity which stated by Hogg and Abraham, there were (1) misidentification, which was experienced by 4 people of Mamak Rumah Bagonjong; those who feel the position of mamak in their people are worthless, (2) social comparison, which was experienced by 4 mamak Rumah Bagonjong and sumando who did not carry out their position according to the functions; from the issues that was so complicated for people of Rumah Bagonjong who experienced by these men, makes the creation of a series of comparisons of the issues which faced with what should happen, and (3) social mobility, experienced by 4 people of mamak Rumah bagonjong; from the issue that befall their people, they make changes and movements to get a solution to the problems they were facing.